Clinical and functional characteristics of youth at clinical high-risk for psychosis who do not transition to psychosis. Issue 10 (4th September 2018) - Addington, Jean; Stowkowy, Jacqueline; Liu, Lu; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; McGlashan, Thomas H.; Perkins, Diana O.; Seidman, Larry J.; Tsuang, Ming T.; Walker, Elaine F.; Bearden, Carrie E.; et al.
Abstract: Background: Much of the interest in youth at clinical high risk (CHR) of psychosis has been in understanding conversion. Recent literature has suggested that less than 25% of those who meet established criteria for being at CHR of psychosis go on to develop a psychotic illness. However, little is known about the outcome of those who do not make the transition to psychosis. The aim of this paper was to examine clinical symptoms and functioning in the second North American Prodrome Longitudinal Study (NAPLS 2) of those individuals whose by the end of 2 years in the study had not developed psychosis. Methods: In NAPLS-2 278 CHR participants completed 2-year follow-ups and had not made the transition to psychosis. At 2-years the sample was divided into three groups – those whose symptoms were in remission, those who were still symptomatic and those whose symptoms had become more severe. Results: There was no difference between those who remitted early in the study compared with those who remitted at one or 2 years. At 2-years, those in remission had fewer symptoms and improved functioning compared with the two symptomatic groups. However, all three groups had poorer social functioning and cognition than healthy controls. Conclusions: A detailed examination of the clinical and functional outcomes of those who did not make the transition to psychosis did not contribute to predicting who may make the transition or who may have an earlier remission of attenuated psychotic symptoms.